Una nueva mirada desde los límites de lo irreal: la fusión de categorías genéricas en la escritura de la imaginación de Juan Jacinto Muñoz Rengel - Álvarez Méndez, Natalia (Studia Romanica Posnaniensia, 2018)
Juan Jacinto Muñoz Rengel (1974) is one of the greatest exponents of the hybridization of the fantastic with other non-mimetic modalities and with popular genre narratives. The mestizaje characterizes, through juxtaposition or fusion, much of his work, generating the ultimate significance of a broader scope. The fantastic is intertwined with adjacent categories, including science fiction, terror and magical realism. It is also commonly combined with the historical, detective, adventure or humorous narrative styles. He merges these diverse modes of invention by transgressing the rigid and normative molds with the aspiration of constructing new literary options. The dissolution of frontiers between the fantastic and other neighboring genres is also potentiated with frequent intertextual nods and suggestive tributes to the traditions of the unusual.